Presenting results in development cooperation: risks and limitations - Sarah Holzapfel (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
With public budgets being increasingly stretched and people becoming more and more sceptical about aid effectiveness, bilateral and multilateral donor organisations are under growing pressure to justify their existence. In order to provide accountability to taxpayers in donor countries, an increasing number of development organisations are now reporting not only on the inputs and resources they provide for development cooperation, but also on the results of the interventions they fund. Using standard indicators, such as the number of teachers trained, development organisations aggregate selected results in priority areas across countries and interventions in order to provide the public with an overview of their contributions to longer-term development progress in partner countries. Reporting on aggregate results can be an effective way of communicating the benefits of development cooperation to the general public and is an important means of bolstering public support for development cooperation. However, this method is not without its problems: it is one-sided in its focus on providing accountability to taxpayers in donor countries, can have a number of adverse effects and is limited in its conclusiveness. Consequently, this analysis aims to identify the limitations and risks of using standard indicators in results reporting and to provide recommendations for designing indicator systems that minimise risk. The analysis shows that reporting on contributions using standard indicators can lead, among other things, to an excessive focus on short-term results that are easy to map using these indicators, to the detriment of longer-term, qualitative outcomes. Additionally, the standard indicators used only have limited explanatory potential, as they merely capture the easily measurable, partial aspects of the total contributions of development organisations. Moreover, the aggregated results reported are not sufficient for evaluating the effectiveness of the aid provided by donor organisations, as it is not possible to assess the influence of the measured contributions on the achievement of longerterm development goals. Due to the limited conclusiveness of the indicators, it is advisable to additionally conduct a greater number of rigorous impact evaluations. These allow the extent of the contributions of individual actors or interventions towards longer-term development results to be assessed in an exemplary manner. Donor organisations should also promote aid transparency and make the results of all publicly financed development cooperation projects freely available at an individual intervention level (in an online database or as part of the International Aid Transparency Initiative Standard, for instance). This will help to ensure that results are recorded in a more comprehensive manner. Moreover, it will enable the public in donor and recipient countries to hold development actors accountable for achieving goals of individual projects and programmes.
Keywords: 330; Regionale + globale + transnationale Governance; Wirksamkeit und Evaluierung